2011
DOI: 10.1371/journal.ppat.1002328
|View full text |Cite
|
Sign up to set email alerts
|

Exhausted Cytotoxic Control of Epstein-Barr Virus in Human Lupus

Abstract: Systemic Lupus Erythematosus (SLE) pathology has long been associated with an increased Epstein-Barr Virus (EBV) seropositivity, viremia and cross-reactive serum antibodies specific for both virus and self. It has therefore been postulated that EBV triggers SLE immunopathology, although the mechanism remains elusive. Here, we investigate whether frequent peaks of EBV viral load in SLE patients are a consequence of dysfunctional anti-EBV CD8+ T cell responses. Both inactive and active SLE patients (n = 76 and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
101
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 43 publications
11
101
3
Order By: Relevance
“…Consistent with the aforementioned immune control in the presence of phenotypically exhausted T-cells, there is evidence that PD-1 high CD8 + T-cells can express similar or even elevated levels of cytotoxic molecules compared to cells with a less pronounced exhausted phenotype 37,[42][43][44][45] .…”
Section: Evidence That Functional T-cells Are Maintained In Chronic Imentioning
confidence: 52%
“…Consistent with the aforementioned immune control in the presence of phenotypically exhausted T-cells, there is evidence that PD-1 high CD8 + T-cells can express similar or even elevated levels of cytotoxic molecules compared to cells with a less pronounced exhausted phenotype 37,[42][43][44][45] .…”
Section: Evidence That Functional T-cells Are Maintained In Chronic Imentioning
confidence: 52%
“…[ [21][22][23] The pathophysiology of EBV reactivation remains uncertain. Recent data suggest that EBV could trigger inflammatory process through interleukin-6 modulation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies indicated defective in vitro CTL function in murine and human lupus (58)(59)(60)(61). Effective CTLs are particularly important in lupus patients in the setting of a concomitant viral infection.…”
Section: Discussionmentioning
confidence: 99%